Kesiapan Belajar Anak Usia Dini: Studi Komparatif Antara Pendidikan di Taman Kanak-Kanak dan Program Calistung Nonformal - Raden Roro Vemmi Kesuma Dewi1, Raden Roro Vemmi Kesuma Dewi; Arief Hidayat2, Arief Hidayat; Widhyanti Rosmaniar, Widhyanti Rosmaniar (STIT Sirojul Falah Bogor, 2025)
Early childhood learning readiness is a crucial indicator in determining the success of the transition from preschool education to elementary school. This study aims to compare the level of learning readiness between children who attended Kindergarten (TK) and those who participated in nonformal literacy and numeracy (calistung) programs. A quantitative-descriptive research approach was employed, involving a sample of 120 children aged 5-7 years who underwent a psychometric test for the New Student Admission (PPDB) process at MI At-Taqwa 15 Babelan Kota. The findings indicate that children with a kindergarten education background demonstrated better learning readiness, as evidenced by higher test scores, well-developed cognitive abilities, and optimal psychological preparedness. In contrast, while children from nonformal calistung programs exhibited greater focus and calmness during the test, their overall results were generally lower. These findings highlight the importance of a play-based learning curriculum in kindergarten to support holistic psychological and cognitive development. This study contributes to the implementation of the PAUD-SD transition program, emphasizing the need for developmentally appropriate learning strategies for young children. The conclusion recommends play-based learning as a fundamental approach to preparing children comprehensively before entering formal schooling. Keywords: learning readiness, early childhood, kindergarten, literacy and numeracy program, play-based education, PAUD-SD transition.